Women's experiences of their maternity care: A principle- based concept analysis. Issue 5 (September 2020) - Beecher, Claire; Devane, Declan; White, Mark; Greene, Richard; Dowling, Maura
Abstract: Background: Despite many countries employing the use of national and large scale regional surveys to explore women's experiences of their maternity care, with the results informing national maternity policy and practice, the concept itself is ambiguous and ill-defined having not been subject of a structured concept development endeavour. Aim: The aim of this review is to report on an in-depth analysis conducted on the concept of 'women's experiences of their maternity care'. Methods: Using the principle-based method of concept analysis by Penrod and Hupcey (2005), the concept of 'women's experiences of their maternity care' was analysed under the epistemological, pragmatic, linguistic and logical principles. The final dataset included 87 items of literature published between 1990 and 2017 retrieved from a systematic search of the MEDLINE, CINAHL, EMBASE and PSYCinfo databases. Findings: The epistemological principle identified that a theoretical definition of the concept is elusive with a variety of implicit meanings. The pragmatic principle supports the utility of the concept in scientific literature, however the lack of a theoretical definition has led to inconsistent use of the concept, as highlighted by the linguistic principle. Furthermore, the logical principle highlighted that as the concept lacks definition blurring is identifiable when theoretically positioned with related concepts. Conclusion: The outcome of this concept analysis is a theoretical definition of a previously undefined concept. This definition highlights the subjective nature of the concept, its dependency upon a woman's individual needs, expectations and circumstances and the influence of the organisation and delivery of maternity care.